Physical, chemical and mechanical properties of cements type CPI and CPV obtained with different proportions of clinker with lime filler (Research, Society and Development, 2021)
In recent decades, the growth of Portland cement production has intensified, given the growth of civil construction. However, the activities of the cement industries are extremely polluting and contribute a large share of CO2 emissions. Having adopted the global focus of increasing additions in Portland cements with a view to developing a more sustainable product, the objective of this work was to identify the potential for replacing part of the clinker in CPI and CPV ARI RS cements. Two types of limestone with a high content of calcium carbonate were used, one with a coarser grain size and the other with a finer grain size, producing different mortars in the laboratory. The influence of additions on chemical characteristics was verified through standardized tests (sulfur trioxide, insoluble residue, loss on fire, magnesium oxide) and physical tests on residue in the 75 micron sieve, hot expandability, paste consistency, onset and end of catch. The results obtained allowed us to verify that, with regard to the chemical aspect, there was a significant and expected increase in the loss to fire for the group of samples containing limestone filler. As for the physical aspects, it was found that there is a strong relationship between the higher compressive strengths and the physical effects provided by the presence of ultrafine particles. The additions resulted in cements with high compressive strengths for all ages, considering a 50% reduction in clinker in the composition of CPI and CPV ARI RS cements.